Analysis of Principal Leadership Style on Teacher Performance: A Literature Review - Arrafi Siraj Adha; Johar Permana (Lembaga Bale Literasi, 2026)
School principals as leaders have various leadership styles according to their character. On the other hand, job satisfaction of teachers is one of the outcomes achieved from the application of the principal's leadership style. This literature study aims to understand the influence and comparison of school principals' leadership styles on teacher performance in various schools with different types and locations. This literature study was conducted by collecting several relevant scientific research articles, with the data collection process carried out through identification, screening, and eligibility, resulting in 10 relevant articles for the research questions. Based on the research results, there are three common leadership styles used by school principals in various schools, namely situational, transformational, and democratic leadership styles. The existing literature finds that the leadership style of the principal has a significant impact on job satisfaction. Democratic leadership style is generally more frequently applied, and this shows that the leadership style of the principal plays a key role in influencing the level of job satisfaction of teachers in schools